Patrimónios alimentares aquém e além-mar - Carmen Soares (DIAITA, 2016)
The studies collected in this volume reflect, in general, upon food given its extraordinary cultural and identity value. With different approaches to food heritage, whether from a linguistic perspective, or from a more literary or cultural analysis, with a due historical, social and spatial framework, the set of papers highlight the importance of this topic, from classical antiquity up to the present day. In fact, food and everything that goes with it lead us on a journey revealing man's way of life and his relationship with nature and other living beings. The thirty-four contributions of this volume are gathered in the following chapters: 1. Food: intangible heritage; 2. Food and literary heritage; 3. Food and linguistic heritage; 4. Food: health and wellbeing; 5. Food: society and culture; 6. Food and intercultural dialogue. With this volume it is also intended to open up perspectives on new research areas of food heritage as an essential source of knowledge for today.